2010
DOI: 10.5194/acp-10-8563-2010
|View full text |Cite
|
Sign up to set email alerts
|

Temperature variability and trends in the UT-LS over a subtropical site: Reunion (20.8° S, 55.5° E)

Abstract: Abstract. This paper mainly focuses on the trends and variability of the UT-LS temperature using radiosonde observations carried out over 16 years (January 1993 to December 2008) from a southern subtropical site, Reunion (20.8 • S, 55.5 • E), using a linear-regression fitting model. Two kinds of tropopause definitions, namely, cold point tropopause (CPT) and lapse rate tropopause (LRT) are used. In order to characterize and quantify the relationship between regional oceanic forcing and temperature at UT-LS, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…To identify the impact of the different modes of variability affecting the SWIO on the lightning activity, we used a statistical model called "Trend-Run" (Bencherif et al, 2006;Bègue et al, 2010). Previously, temperature trends and variations over 2 subtropical sites (Durban and La Réunion) have been studied with this model using monthly mean radiosonde temperature profiles (for the periods 1980-2001 and 1993-2008, respectively).…”
Section: Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the impact of the different modes of variability affecting the SWIO on the lightning activity, we used a statistical model called "Trend-Run" (Bencherif et al, 2006;Bègue et al, 2010). Previously, temperature trends and variations over 2 subtropical sites (Durban and La Réunion) have been studied with this model using monthly mean radiosonde temperature profiles (for the periods 1980-2001 and 1993-2008, respectively).…”
Section: Variabilitymentioning
confidence: 99%
“…Recent results by Morioka et al (2010) revealed that IOD acts as a major climate mode in the SWIO. Thus, the IOD has been included (Bègue et al, 2010) using the Dipole Mode Index (Behera and Yamagata, 2003) defined as the difference in SST between the western and eastern tropical Indian Ocean. Since the MJO is the dominant intra-seasonal mode of variability in the tropics (Zhang, 2005), this forcing has also been added in Trend-Run.…”
Section: Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…1) considers the main parameters such as annual (AC) and semi-annual cycles Ann. Geophys., 36, 301-310, 2018 www.ann-geophys.net/36/301/2018/ (SAC), QBO (quasi-biennial oscillation), ENSO (El Niño-Southern Oscillation), and the 11-year cycle (Sunspot Number), in addition to a residual term ε, assuming a consistent trend (Bègue et al, 2010). In this way, the contribution that each of these cycles or oscillations makes to the temperature variance may be estimated.…”
Section: Trend-run Modelmentioning
confidence: 99%
“…While interest to some degree has moved from the tropical to the extratropical UTLS region (e.g. Bègue et al, 2010), the polar regions, reviewed by e.g. Highwood et al (2000), are still poorly covered.…”
Section: Introduction and Data Sourcesmentioning
confidence: 99%